Odour source localization strategy for multiple robots using swarm intelligence with odour-gated anemotaxis - Syed Muhammad Mamduh Syed Zakaria (School of Mechatronic Engineering, 2017)
This research will focus on gas/odour source localization problem. This term specifically refers to the conditions where the target gas is dispersed in the air. Similar researches has reported and described chemical source localization and dispersion in water; it is still no different than airborne chemical sensing as the chemical is tracked in a fluid. The dispersion of the chemical in these two environments would be congruent and would be subject to conventional fluid mechanics theory. Therefore, the rest of the chapters will loosely use the term gas/odour source localization to refer to the airborne chemical source localization task. The theories discussed however, may be used in both environments and as such research on chemical dispersion in water environment will be referenced in this document.